Optimizing Tourism Promotion Strategies Through Social Media - Prastiwi, Daning Kurnia; Indra Bhaskara, Gde; Narottama, Nararya (Udayana Journal of Social Sciences and Humanities, 2024)
This study analyzes the promotional strategy of Superlative Gallery through social media, focusing on Instagram, X, and TikTok. Superlative Gallery is the first NFT art gallery in Indonesia and Southeast Asia, utilizing social media as its primary promotional tool. While Instagram and X have been optimized, TikTok remains underutilized, with only 21 followers compared to over 8000 followers on other platforms. Using a descriptive qualitative method, data were collected through observation, documentation, and unstructured interviews. Data analysis was conducted using the SOSTAC and SWOT approaches, as well as social media analysis tools like Instagram Insights. The research findings produced 8 strategies, 9 tactics, and 10 action plans to enhance Superlative Gallery's presence on social media, particularly in optimizing the use of TikTok as the main promotional platform. This study provides a guide to improving the effectiveness of Superlative Gallery's digital promotion in the future